Correlation analysis of solar wind events at difference hemispheric symmetry based on geomagnetic parameters / Dalila Shafie - Shafie, Dalila (2010)
The sun, the earth, and the space in-between are all connected. It creates many of space activities such as solar wind. Solar wind is responsible for such phenomena as geomagnetic storm, sub storm and aurora. Geomagnetic storm disturbances have been affecting electrical systems on the ground such as such as pipelines corrosion, power systems blackouts, railway tracks problems and disrupt cell phone communication systems. This paper presents the analysis of magnetic data by using raw data taken from Magnetic Data Acquisition System (MAGDAS) station at difference hemispheric which is at Onagawa, Japan station for Northern region and Manado, Indonesia station for equatorial region. Three components were used to analyze this variation which is H, D, and Z component. There are three events due to solar wind that are chosen to be analyzed by using MATLAB program. The events are on 9,h April 2006,14th April 2006, and 19"1 August 2006. The change in magnetic field AH was calculated to show the variation in H parameter. The events are then compared with Disturbance storm-time (Dst) that are taken from Kyoto University, Japan.